2019
DOI: 10.3389/fimmu.2019.01212
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-Independent Protection Against Invasive Pneumococcal Infections Conferred by Live Vaccine With lgt Deletion

Abstract: Streptococcus pneumoniae is the most common respiratory bacterial pathogen among cases of community-acquired infection in young children, older adults, and individuals with underlying medical conditions. Although capsular polysaccharide-based pneumococcal vaccines have contributed to significant decrease in invasive pneumococcal infections, these vaccines have some limitations, including limited serotype coverage, lack of effective mucosal antibody responses, and high costs. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 79 publications
2
19
0
3
Order By: Relevance
“…Recently, we showed that intranasal immunization of mice with live S. mitis induces serotype-independent protection against infections with pneumococcal serotypes 2 and 4, which was associated with enhanced IgG and IgA responses (13). Likewise, vaccination with attenuated S. pneumoniae serotype 4 provided serotype-independent protection against invasive pneumococcal infections (22). The reason behind this serotype-independent immune response could be explained by the similarity between the nature of capsular and protein antigens of S. mitis and S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that intranasal immunization of mice with live S. mitis induces serotype-independent protection against infections with pneumococcal serotypes 2 and 4, which was associated with enhanced IgG and IgA responses (13). Likewise, vaccination with attenuated S. pneumoniae serotype 4 provided serotype-independent protection against invasive pneumococcal infections (22). The reason behind this serotype-independent immune response could be explained by the similarity between the nature of capsular and protein antigens of S. mitis and S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, lgt converts pre‐prolipoprotein into prolipoprotein by adding diacyl lipid chains to lipoproteins (Wichgers Schreur et al., 2011). Thus, the deletion of lgt gene has been widely used to prepare lipoprotein‐deficient bacteria (Jang et al., 2019; Kang et al., 2018; Kim et al., 2018; Mohammad et al., 2020). However, lgt ‐deleted S. gordonii mutant strain still would have pre‐prolipoproteins in the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 99%
“… Jang et al. (2019) developed a live attenuated vaccine with a strain TIGR4 lgt-mutant of S. pneumoniae.…”
Section: Non-capsular Vaccines Alternativesmentioning
confidence: 99%
“…(2019) developed a live attenuated vaccine with a strain TIGR4 lgt-mutant of S. pneumoniae. Lgt gene codifies the Lipoprotein diacylglyceryl transferase (Lgt) ( Jang et al., 2019 ), which participates in the production of lipoproteins in the bacterium. Lipoproteins are essential in several physiological roles in bacteria, for example, cell division, conjugation, adhesion, and immune evasion.…”
Section: Non-capsular Vaccines Alternativesmentioning
confidence: 99%